PWDs accessibility audit: commercial complexes, Klang Valley, Malaysia / Ahmad Ezanee Hashim … [et al.] - Hashim, Ahmad Ezanee; Samikon, Siti Aida; Ismail, Faridah; Kamarudin, Hikmah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Barriers may restrict the mobility of people with disabilities (PWDs) in a building. This research identifies the effectiveness of accessibility in commercial complexes in the Klang valley in the state of Selangor Malaysia. Data were based from semi structured interviews and site audit with four groups of respondents of different type of disability. The finding reveals it is mandatory requirements to provide user friendly accessibility within and outside buildings as there are weaknesses found such as poor thought out solution, poor quality materials, limited guidelines and weak enforcement by the relevant authorities. The findings highlighted could be a benchmark for PWDs building industry in developing a user friendly and accessible building environment in commercial complexes.